The costs of access to playing tennis in selected countries of the world: An introductory study - Kaczmarek, Aleksander (ITF Coaching & Sport Science Review, 2018)
While many studies have focused on the financial situation of professional team sports, little attention has been paid by research to individual sports from an economic point of view. The aim of this article is to provide some initial data on the cost of access to tennis in different countries in the world. It is hoped that these figures will assist in providing a better understanding of the participation landscape worldwide in order to design and deliver the appropriate development policies needed by the end users.